Adipose Tissue Properties in Tumor-Bearing Breasts - Miran, Isabelle; Scherer, Dominique; Ostyn, Pauline; Mazouni, Chafika; Drusch, Françoise; Bernard, Marine; Louvet, Emilie; Adam, Julien; Mathieu, Marie-Christine; Haffa, Mariam; Antignac, Jean-Philippe; Le Bizec, Bruno; et al. (Frontiers in Oncology, 2020)
The tissue stroma plays a major role in tumors’ natural history. Important programs for tumor progression such as epithelial-mesenchymal transition are not activated as cell-autonomous processes but under the conditions of cross talk between tumor and stroma. Adipose tissue is a major component of breast stroma. This study compares breast adipose tissues in women with breast tumors to those in healthy women with the ultimate aim of defining a signature that could be translated into biomarkers for cancer risk. In tumor-bearing breasts, we sampled adipose tissues adjacent to, or distant from the tumor. Parameters studied included: adipocytes size and density, immune cell infiltration, vascularization, secretome and gene expression. Adipose tissues from tumor-bearing breasts, whether adjacent to or distant from the tumor, do not differ from each other by any of these parameters. By contrast, adipose tissues from tumor-bearing breasts have the capacity to secrete twice as much interleukin 8 (IL-8) than those from tumor-free breasts and differentially express a set of 200 genes of which many belong to inflammation and integrin signaling pathways. These observations show that adipose tissues from tumor-bearing breasts display unique constitutive properties. We propose that these properties contribute to the permissiveness of the breast tissue to tumor growth as a non-cell autonomous process.